2017
DOI: 10.1186/s13063-017-2259-y
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial and economic evaluation of nurse-led group support for young mothers during pregnancy and the first year postpartum versus usual care

Abstract: BackgroundChild maltreatment is a significant public health problem. Group Family Nurse Partnership (gFNP) is a new intervention for young, expectant mothers implemented successfully in pilot studies. This study was designed to determine the effectiveness and cost-effectiveness of gFNP in reducing risk factors for maltreatment with a potentially vulnerable population.MethodsA multi-site, randomized controlled, parallel-arm trial and prospective economic evaluation was conducted, with allocation via remote rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…The absence of evidence for the effectiveness of the current intervention program in high-risk adolescent mothers in Germany is also in line with recent RCTs (Barnes et al, 2017; Robling et al, 2016) in other countries. An intervention for adolescent mothers, which has previously shown to be effective in adolescent mothers in the United States to enhance parental care (Olds, Henderson, Chamberlin, & Tatelbaum, 1986), was not effective in the UK for reducing child maltreatment risk or enhancing parental caregiving behaviors in this high-risk group.…”
Section: Discussionsupporting
confidence: 63%
“…The absence of evidence for the effectiveness of the current intervention program in high-risk adolescent mothers in Germany is also in line with recent RCTs (Barnes et al, 2017; Robling et al, 2016) in other countries. An intervention for adolescent mothers, which has previously shown to be effective in adolescent mothers in the United States to enhance parental care (Olds, Henderson, Chamberlin, & Tatelbaum, 1986), was not effective in the UK for reducing child maltreatment risk or enhancing parental caregiving behaviors in this high-risk group.…”
Section: Discussionsupporting
confidence: 63%
“…18,19 An implementation evaluation reported progress in the delivery of the programme in 10 test sites. 20 The differing pattern of service provision and sociocultural context meant that the relative costs and benefits of the programme needed to be replicated in England before widespread implementation could be recommended. This was an explicit licensing requirement of the programme, and the stimulus for the BB:0-2 trial (ISRCTN23019866) of the FNP.…”
Section: Specialist Home Visiting: the Family Nurse Partnershipmentioning
confidence: 99%
“…25 A trial assessing the effectiveness and cost-effectiveness of group FNP in England to reduce risk factors for maltreatment found no differences for child abuse potential and parent-infant interaction at 12 months. 20 Pro Kind is a German adaptation of the NFP; it was trialled between 2006 and 2012 with 755 first-time mothers. 28 A current study to evaluate the medium-term impact of Pro Kind (to age 7 years) will assess maltreatment by parental self-report and also assess child development and school achievement.…”
Section: Other Evaluations Of the Nurse-family Partnershipmentioning
confidence: 99%
“…The primary outcome effects of most studies were non‐significant, as were the effects on QALYs, with the exception of one trial on the effectiveness of cognitive therapy for PTSD (Shearer et al., 2018). In four trials, negative QALY effects were found (Anderson et al., 2014; Barnes et al., 2017; Goodyer et al., 2017; Sayal et al., 2016). It is difficult to see the relevance of a cost–utility analysis in the absence of a QALY gain of the intervention, except maybe when a small negative effect is outweighed by much lower expenses compared to care as usual.…”
Section: Child and Adolescent Mental Health Economics In Practicementioning
confidence: 99%